Cooking with Dionysus's Wine - Tsappa, Lilian (My University, 2022)
This article explores the historical connections between the land, Gods and wineproduction in Cyprus through the culinary lens. A overview of Greek Mythological folklore in and around Cyrprus is given, then the development of wine production from the middle ages to modern times is shared. The author’s family history is contextualised in the rich history of Cypriot wine production and connected to the art of cooking with wine. The recipe shared is that of the writer’s father and has been shared across generations.